Airborne Lead (Pb) From Abandoned Mine Waste in Northeastern Oklahoma, USA. (4th September 2020) - Li, Junran; McDonald‐Gillespie, Julie
Abstract: Active and abandoned mines pose serious health threats to humans, aquatic, and terrestrial biota. Northeastern Oklahoma, home to a number of Native American Tribes, is part of the well‐known Tri‐State Mining District. More than 100 years of mining production in this area has left numerous, large chat piles in the surrounding environment. Despite numerous studies and efforts on the restoration of metal contamination in this area, no studies have attempted to distinguish the contributions of different sources, particularly from the atmospheric deposition, of metals to the aquatic environment. Here, we analyzed the atmospheric deposition of Pb from Picher, a town surrounded by chat piles, and Tulsa, a primary metropolitan area in northeastern Oklahoma, from 2010 to 2016. We found that chat piles in Picher contain ~20% and 6% of fine particles that are subjective to windborne transport and human inhalation, respectively, and these fine particles contain disproportionally high concentrations of Pb. Despite the absence of industrial and human activities, airborne Pb in Picher is 2–5 times higher than that of Tulsa. A conservative estimate showed that airborne Pb may contribute up to 10% of annual Pb mass flux to a lake 18 km away from the chat piles in Picher and probably a much higher contribution for soil and water located adjacent to Picher. Despite known limitations, our study represents the first attempt to evaluate the significance of Pb‐laden airborne particulate matter from a large‐scale abandoned mining area where the humans are particularly vulnerable to metal exposure. Key Points: The characteristics of airborne Pb associated with a large abandoned mining area in northeastern Oklahoma were examined Mining waste contains ~20% and 6% of fine particles that are subjective to windborne transport and human inhalation, respectively Airborne Pb in the mining area is 2–5 times higher than Tulsa, Oklahoma, and contributes 10% of Pb in lake sediment close to the mining area